Resolva a Equação:
Anexos:
![](https://pt-static.z-dn.net/files/da1/6d8a4302a318e19a10890847728e074d.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
2 x x 2 x
1 2 1 1 2 = 12
3 1 2 3 1
8 + 3x + x - (6x + 2 + 2x) = 12
8 +3x + x -6x -2 - 2x - 12 = 0
8 + 3x +x -6x - 2x -2 - 12 = 0
8 - 4x -14 = 0
-4x = 14 - 8
-4x = 6
x = -6/4
x = -3/2
Explicação passo-a-passo:
Respondido por
0
Resposta:
x = - 3/2
Explicação passo-a-passo:
2 x x 2 x
1 2 1 1 2 = 12
3 1 2 3 1
2.2.2 + x.1.3 + x.1.1 - [x.2.3 + 2.1.1 + x.1.2] = 12
8 + 3x + x - [6x + 2 + 2x] = 12
8 + 4x - [8x + 2] = 12
8 + 4x - 8x - 2 = 12
- 4x + 6 = 12
- 4x = 12 - 6
- 4x = 6 (-1)
4x = - 6 (:2)
2x = - 3
x = - 3/2
Perguntas interessantes